Crystalline Properties of Jambu (Syzygium aqueum (Burm. f.) Alston) and Jackfruit (Artocarpus heterophyllus) Seed Starches: An XRD Spectroscopic Study - Wattimena, Synodalia; Patty, Philipus (LPPM Universitas Mataram, 2025)
Starch, a complex carbohydrate found in plants, has become an alternative raw material to make plastics (bioplastics). Bioplastics have been intensively used to replace conventional plastics, which cannot be degraded and thus cause environmental problems. Therefore, starch has been the focus of many studies, where researchers study its properties, such as crystalline properties. These properties influence the properties of starch-based bioplastics: their mechanical strength, water resistance, and degradation rate are affected by the arrangement of starch molecules into crystalline structures. This study aims to characterize crystalline properties of starches of jambu fruit (Syzygium aqueum (Burm. f.) Alston) and jackfruit seeds (Artocarpus heterophyllus). For this purpose, X-ray diffraction (XRD) spectroscopy was used. The results show that the starches of jambu and jackfruit fruit seeds belong to different types: B-type starch for jambu and A-type starch for jackfruit. The index of crystallinity of starch of jackfruit seed, 54.0%, is higher than that of starch of jambu fruit seed, 38.1%. Starch of jackfruit seed has higher crystalline properties compared to starch of jambu seed.